Carriacou : a reconnaisance survey - Buckmire, K.U. (CARDI CastriesLC, 1985)
Describes the cropping and livestock farming systems of Carriacou Island in order to determine land use and ascertain traditions and beliefs that influence such systems. Highlights constraints to production and productivity viz. unavailability of fertilizer, soil erosion, lack of water conservation, overgrazing, and poor genetic potential of animals. Makes recommendations which include soil, water and forage conservation techniques, pest, parasite, weed and wild dog control and genetic improvement of animals.